Proof of Acacia nilotica stand expansion in Bekol Savanna, Baluran National Park, East Java, Indonesia through remote sensing and field observations - SUTOMO SUTOMO; EDDIE VAN ETTEN; LUTHFI WAHAB (Biodiversitas Journal of Biological Diversity, 2016)
utomo, van Etten E, Wahab L. 2016. Proof of Acacia nilotica stand expansion in Bekol Savanna, Baluran National Park,East Java, Indonesia through remote sensing and field observations. Biodiversitas 17: 96-101. One of woody species that is known toinhabit certain savanna ecosystems is Acacia nilotica. The Acacia nilotica tree is widespread in the northern savannah regions, and itsrange extends from Mali to Sudan and Egypt. Acacia nilotica was first introduced to Java Island in 1850. It then spread to Bali, EastNusa Tenggara, Timor and Papua. Found in grasslands, savanna is reported as important colonizer at Baluran National Park in East Javaand Wasur National Park Papua. We conducted Vegetation analysis in three areas of the Baluran Savanna namely: Grazed, burned andunburnt. Our observation result analysis showed that in terms of the three most important tree species in all of the sites that we sampled (grazed, burnt and unburnt savannas) Acacia nilotica appeared in each of these sites. The values however, vary between sites. Acacia nilotica Importance Value Index is highest in the unburnt savanna, with IVI reaching almost 250. The unburnt site is actually a burnt site but with moderate age or time since fire (approximately 6-7 years), whereas the burnt site is savanna with relatively young age/time since fire (few months to 1 year).Â We also conducted GIS analysis using Satellite Images (October 2013 and October 2014) to pick up changes in Bekol savanna. Result showed that expansion of A. nilotica stand occurred towards the savanna. Over dominance of the woody species A. nilotica could shift the savanna into another ecosystem state, i.e. secondary forest.